Death and dying - Albert-Ludwigs-Universität Freiburg - Sonderforschungsbereich 948 "Helden - Heroisierungen - Heroismen" (2024)
Abstract: In many cultures mortality is a prerequisite for heroism. This is because death is seen as a risk that heroes take, a sacrifice they make, and thus the ultimate transgression. Both the willingness to die, and death and its circumstances play an essential role in heroization processes. The adoration and admiration of heroes do not end with their lives, but continue or, in some cases, emerge posthumously. Death and dying play a role in heroization processes in two ways: 1. In the case of ‘heroic death’, death and its circumstances form a distinct factor for the heroization of a figure. Typically, this is a retrospective heroization which goes hand in hand with the attribution that a hero exposed himself to a dangerous situation at the risk of, or in the certainty of, his own death and thus made a self-sacrifice. The hero’s inner attitude towards death thus becomes a decisive criterion of heroization – often irrespective of whether this attitude was genuine or whether it was a mere projection by admirers. 2. The ‘death of a hero’ primarily means no more than the death of a figure who had already achieved heroic status during their lifetime. The death of a hero is often an occasion for the community of admirers to recall his/her deeds and actions and to reaffirm his/her heroic status. Such an event is therefore often associated with ritual tributes, commemorative practices, mortuary and funerary cults